SOME OBSERVATIONSO N THE PERFORMANCE OF IO.S m MID .. WATER TRAWl OPERATED OFF VERA VAl - SIVAN, T M; DESHPANDE, S D; RAMARAO, S V.S (Fishery Technology, 2025)
The communication presents the results of fishing trialsconducted off Veraval with a 10.5 m four-seam unequal paneledmid-water trawl with vertically curved otter boards. The design andstructural details of net and otter boards are described in detail.Particulars such as the fish caught during experimentation, horizontalspread of the net as well as towing resistance offered in action arealso incorporated.